(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Proper definition and implementation of NFRs is critical. In case they are Over-specify, then the solution may be too costly to be viable; in case they are underspecified or underachieve them, the system will be inadequate for its intended use. An adaptive and incremental approach to exploring, defining, and implementing NFRs is vital for the successful delivering of NFRs. NFRs are not product backlog items. The constraints on development that limit degree of design freedom while building system. These constraints are articulated in the acceptance criteria for multiple product backlog items. For e.g., SAML-based Single Sign-on - SSO is a requirement for the product. SSO is a functional requirement, while SAML is the constraint. In that sense, any backlog item building sign-on functionality would reference the SAML constraint in its acceptance criteria. The sections that follow describe the phases of NFR journey from discovery to deployment for a large complex business critical systems including the NFR modelling framework.